Health-related quality of life in adult patients with asthma according to asthma control and severity: A systematic review and meta-analysis - Oh, Byeong-Chan; Lee, Ju-Eun; Nam, Jin Hyun; Hong, Ji-Yoon; Kwon, Sun-Hong; Lee, Eui-Kyung (Frontiers in Pharmacology, 2022)
Background: The utility values are increasingly being used in economic evaluations and health policy decision making. This study aims to conduct a systematic literature review and meta-analysis of the utility values for asthma, particularly with respect to severity and asthma control. Materials and methods: A literature search was conducted using the MEDLINE, Embase, and Cochrane Central Register of Controlled Trials databases for studies published until July, 2020, reporting the utilities of adult asthma. We extracted utility values derived by nine indirect and four direct utility instruments. Meta-analyses were performed for each utility instrument according to health states based on the level of asthma control and severity. Results: Fifty-two eligible studies were included in our systematic review, of which forty studies were used in the meta-analyses. Among the 13 utility instruments, the most used was EQ-5D-3L, whereas EQ-5D-5L showed the narrowest 95% confidence interval (95% CI, 0.83–0.86) of pooled utility. The pooled utility of asthma declined with worsening control levels and severity. The pooled utility value of EQ-5D-3L was 0.72 (95% CI, 0.63–0.80) for uncontrolled, 0.82 (95% CI, 0.75–0.88) for partly controlled, and 0.87 (95% CI, 0.84–0.90) for well-controlled asthma. Conclusions: Our study shows that EQ-5D-3L and EQ-5D-5L are appropriate for economic evaluations in terms of availability and variability of information, respectively. Asthma patients had poorer utility values with worsened severity and level of asthma control. This study will be useful for health economists conducting economic evaluations of asthma treatments.